Trio Album for Violin, Violoncello and Piano Vol. IV No. 154 - ARENSKY, A (The Boston Music Co., 1913)
Arensky, A....ElegienBethoven L, Van.....AdagionDvorak.....Slavic dancenFaure G......Melody in DnGounod........SerenadenMartini padre G.B......Gavotte